2010
DOI: 10.1177/0033688210380558
|View full text |Cite
|
Sign up to set email alerts
|

The Categorical Facilitation Effects on L2 Vocabulary Learning in a Classroom Setting

Abstract: In the field of vocabulary acquisition, there have been many studies on the efficacy of word lists. However, very few of these were based on research in a classroom setting, and therefore, their results may not be applicable to standard classroom situations. This study investigated which of the five types of word lists (synonyms, antonyms, categorical, thematic, and arbitrary) facilitated L2 vocabulary learning in a classroom setting. The participants were classified into four clusters according to their learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…However, the findings of this study were in line with the obtained results by the below research studies: According to Hoshino (2010) or Hashemi and Gowdasiaei (2005), introducing new vocabularies through categorical lists or lexical set of words aided learners foster their vocabulary learning. In the case of Cairns et al (2004), they investigated the first-grade students in order to detect homonyms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the findings of this study were in line with the obtained results by the below research studies: According to Hoshino (2010) or Hashemi and Gowdasiaei (2005), introducing new vocabularies through categorical lists or lexical set of words aided learners foster their vocabulary learning. In the case of Cairns et al (2004), they investigated the first-grade students in order to detect homonyms.…”
Section: Discussionsupporting
confidence: 91%
“…In this respect, Hoshino (2010) examined the relative effect of five set of word lists such as synonymous, antonymous, categorical, thematic, and arbitrary word lists on learners' L2 vocabulary learning. Based on the findings, he concluded that presenting new vocabularies through categorical lists promoted learners' vocabulary learning.…”
Section: Introductionmentioning
confidence: 99%
“…It is also considered as a necessary component for improving competency in all areas of communication among users of a language (Celik & Toptas, 2010;Hoshino, 2010). It is a unique constituent that connects the four language skills of speaking, listening, reading and writing together.…”
Section: Background To the Studymentioning
confidence: 99%
“…L1-L2) which suggests that the impact of semantic clustering was only partial. Another study which gives more evidence in favor of semantic clustering is that of Hoshino (2010). Hoshino compared and contrasted five different types of lexical clustering: synonyms, antonyms, category, thematic, and unrelated.…”
Section: Empirical Research On Semantic Clusteringmentioning
confidence: 99%